COMPARATIVE STUDY OF GROSS PROFIT MARGIN AND NET PROFIT MARGIN AT THE TOBACCO COMPANIES PT GUDANG GARAM TBK AND PT HM SAMPOERNA TBK - Munandar, Aris; Darmawan, Imam (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
The financial performance of tobacco companies in Indonesia can be measured using a financial ratio approach. To compare the financial performance of tobacco companies listed on the Indonesia Stock Exchange, a profitability ratio approach can be used, specifically the Gross Profit Margin ratio and the Net Profit Margin ratio. The purpose of this study is to compare the financial performance of PT Gudang Garam Tbk (GGRM) with PT HM Sampoerna Tbk (HMSP) in terms of the Gross Profit Margin ratio and the Net Profit Margin ratio. This study uses ratio analysis and statistical analysis methods, employing an independent sample test with research samples from the years 2013-2022 for both objects of study. The results indicate that PT Gudang Garam Tbk (GGRM) and PT HM Sampoerna Tbk (HMSP) are in a less favorable condition in terms of the Gross Profit Margin ratio, as both companies have not been able to maximize their gross profit earnings. In terms of the Net Profit Margin ratio, PT Gudang Garam Tbk (GGRM) and PT HM Sampoerna Tbk (HMSP) are also in a less favorable condition, meaning that both companies have not been able to maximize their net profit earnings. In conclusion, PT Gudang Garam Tbk (GGRM) and PT HM Sampoerna Tbk (HMSP) are both in a similarly unfavorable condition in terms of maximizing profits.